FORMATION AND DEVELOPMENT OF PROFESSIONAL COMPETENCE OF FUTURE KINDERGARTENERS (Academia Science Repository, 2023)
This article talks about the goals and tasks of the educational concept, the creative approach of the educator in the process of teaching children, the social competence of the educator of the preschool education organization.